Intrinsically Disordered Domain of Kinesin-3 Kif14 Enables Unique Functional Diversity - Zhernov, Ilia; Diez, Stefan; Braun, Marcus; Lansky, Zdenek (Current biology, 2020)
In addition to their force-generating motor domains, kinesin motor proteins feature various accessory domains enabling them to fulfill a variety of functions in the cell. Human kinesin-3, Kif14, localizes to the midbody of the mitotic spindle and is involved in the progression of cytokinesis. The specific motor properties enabling Kif14's cellular functions, however, remain unknown. Here, we show in vitro that the intrinsically disordered N-terminal domain of Kif14 enables unique functional diversity of the kinesin. Using single molecule TIRF microscopy, we found that Kif14 exists either as a diffusible monomer or as processive dimer and that the disordered domain (1) enables diffusibility of the monomeric Kif14, (2) renders the dimeric Kif14 super-processive and enables the kinesin to pass through highly crowded areas, (3) enables robust, autonomous Kif14 tracking of growing microtubule tips, independent of microtubule end-binding (EB) proteins, and (4) is sufficient to enable crosslinking of parallel microtubules and necessary to enable Kif14-driven sliding of antiparallel ones. We explain these features of Kif14 by the observed diffusible interaction of the disordered domain with the microtubule lattice and the observed increased affinity of the disordered domain for GTP-bound tubulin. We suggest that the disordered domain tethers the motor domain to the microtubule providing a diffusible foothold and a regulatory hub, tuning the kinesin's interaction with microtubules. Our findings thus exemplify pliable protein tethering as a fundamental mechanism of molecular motor regulation.
Keywords: vnitřně neuspořádané proteiny; Spindle Apparatus; Cytokinesis; onkogenní proteiny; vazba proteinů; cytokineze; aparát dělícího vřeténka; Protein Binding; kineziny; Oncogene Proteins; lidé; Humans; mikrotubuly; Microtubules; Kinesins; Intrinsically Disordered Proteins